TENDENSI KECURANGAN AKUNTANSI: PENGENDALIAN INTERNAL, LOVE OF MONEY, DAN INTEGRITAS - Maghfirah, Maghfirah; Afrianandra, Cut; Fitri, Fauziah Aida (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This research aims to investigate the impact of internal control, love of money, and integrity on accounting fraud tendencies at the operations head office of PT. Bank Aceh Syariah. The study sample comprises staff in various roles, including customer service, tellers, accounting division, and finance officers, totaling 81 respondents. The research employed the purposive sampling method, and primary data were obtained through questionnaires administered to the participants. The analytical approach utilized multiple linear regression analysis. The findings reveal that, both simultaneously and partially, internal control, love of money, and integrity significantly influence the tendency of accounting fraud at PT. Bank Aceh Syariah's operations head office.